Fogarty catheter: An indispensable tool to complement the ingenuity of the endoscopist for extraction of airway "foreign body with a hole" - Ruchira Nandan; Minu Bajpai; Devendra Kumar Yadav; Prabudh Goel (Wolters Kluwer Medknow Publications, 2022)
Introduction: The extraction of smooth spherical objects is challenging as they are difficult to grasp within the jaws of the forceps and tend to slip distally. Objective: The authors herein have shared their experience with the use of a Fogarty catheter (FC) for safe extraction of smooth and spherical "foreign body (FB) with a hole." Materials and Methods: Report on pediatric cases (n = 4) of airway "FB with a hole" wherein the FC was used for their extraction. Mean age was 27.5 months (range: 17 months-39 months). The male: female ratio was 3:1. The technique of FB extraction with a FC has been described, including the principle of the technique, indications, and contra-indications, technical problems and troubleshooting. Results: The FB spectrum included a necklace bead (n = 2), nonnecklace bead (n = 1) and a fragmented end-piece of the housing of a ball-pen (n = 1). The locations of the FBs were right main bronchus (n = 1), secondary bronchus on the right (n = 1), and in the left main bronchus (n = 2). Successful removal of FB with use of FC during rigid broncoscopy was possible. The bead had to be rotated in n = 2 patients to align the hole with the FC. Problems associated with threading the hole and disimpaction of the FB have been highlighted. No complications were observed. The advantages and limitation of the technique have been discussed. Conclusions: The use of FC with the described technique offers a safe, effective and reproducible method for removal of airway "FB with a hole" in a controlled environment while minimizing the possibility of iatrogenic injury to the wall of the surrounding airways.